Mechanisms of Naturally Acquired Immunity to Streptococcus pneumoniae - Ramos-Sevillano, Elisa; Ercoli, Giuseppe; Brown, Jeremy S. (Frontiers in Immunology, 2019)
In this review we give an update on the mechanisms of naturally acquired immunity against Streptococcus pneumoniae, one of the major human bacterial pathogens that is a common cause of pneumonia, septicaemia, and meningitis. A clear understanding of the natural mechanisms of immunity to S. pneumoniae is necessary to help define why the very young and elderly are at high risk of disease, and for devising new prevention strategies. Recent data has shown that nasopharynx colonization by S. pneumoniae induces antibody responses to protein and capsular antigens in both mice and humans, and also induces Th17 CD4+ cellular immune responses in mice and increases pre-existing responses in humans. These responses are protective, demonstrating that colonization is an immunizing event. We discuss the data from animal models and humans on the relative importance of naturally acquired antibody and TH17 cells on immunity to S. pneumoniae at three different anatomical sites of infection, the nasopharynx (the site of natural asymptomatic carriage), the lung (site of pneumonia), and the blood (site of sepsis). Mouse data suggest that CD4+ Th17 cells prevent both primary and secondary nasopharyngeal carriage with no role for antibody induced by previous colonisation. In contrast, antibody is necessary for prevention of sepsis but CD4+ cellular responses are not. Protection against pneumonia requires a combination of both antibody and Th17 cells, in both cases targeting protein rather than capsular antigen. Proof of which immune component prevents human infection is less easily available, but two recent papers demonstrate that human IgG targeting S. pneumoniae protein antigens is highly protective against septicaemia. The role of CD4+ responses to prior nasopharyngeal colonisation for protective immunity in humans is unclear. The evidence that there is significant naturally-acquired immunity to S. pneumoniae independent of anti-capsular polysaccharide has clinical implications for the detection of subjects at risk of S. pneumoniae infections, and the data showing the importance of protein antigens as targets for antibody and Th17 mediated immunity should aid the development of new vaccine strategies.